Leveraging Agriculture for Nutrition in South Asia (LANSA) research influences nutrition-sensitivity of Bangladesh National Food Policy and Country Investment Plans - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
The Bangladesh National Food Policy and Country Investment Plans over three years (2015-17) made direct reference to Leveraging Agriculture for Nutrition in South Asia (LANSA) research, with the focus in the next phase being on nutrition-sensitive food systems.